2019
DOI: 10.1002/ccr3.2221
|View full text |Cite
|
Sign up to set email alerts
|

Erecta dislocation of the shoulder joint—A rare injury: About four cases

Abstract: A nonresolving axillary nerve injury is a rare associated complication to an inferior dislocation of the shoulder joint. This worsen the midterm outcome of the shoulder. So, neurovascular status must be checked by regular clinical testing and by an electromyography in all cases of inferior dislocation of the shoulder joint.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Posterior dislocations are far less common (2–5 %) and only rarely cause neurovascular disruption [16]. Inferior dislocations are the least common (<0.5 %) type of dislocation, often caused by hyperabduction, and pose the highest risk for axillary artery and brachial plexus injury [17]. Our patient’s dislocation was inferior and complicated by axillary artery involvement.…”
Section: Discussionmentioning
confidence: 96%
“…Posterior dislocations are far less common (2–5 %) and only rarely cause neurovascular disruption [16]. Inferior dislocations are the least common (<0.5 %) type of dislocation, often caused by hyperabduction, and pose the highest risk for axillary artery and brachial plexus injury [17]. Our patient’s dislocation was inferior and complicated by axillary artery involvement.…”
Section: Discussionmentioning
confidence: 96%
“…In our case, the singular and fixed attitude of the arm elevated and hyperabducted at the shoulder and the forearm and the hand pronated lying behind the head, with the humeral head prominence visible and palpable in the axilla, helped us in the diagnosis before the radiographic examination. It is distinctive of LEH an abducted arm over 90° [ 1 ]. Some complications are reported for the LEH as fractures of acromion, greater tuberosity, humeral head, glena, clavicle, coracoid, furthermore, may be present with the LEH glenohumeral cartilage or capsular defects, rotator cuff and labral tears, humeral avulsion of glenohumeral ligament, disruptions of the adjacent muscles [ 5 , 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Luxatio erecta humeri (LEH) is an unusual injury. This dislocation is described in a series of cases reported in the literature [ 1 - 7 ] and recently identified a total of 199 patients [ 8 ]. Most cases can be treated with closed reduction and immobilization, but in case of irreducibility, it requires reduction under general anesthesia and/or further operative measures.…”
Section: Introductionmentioning
confidence: 99%
“…In our case, the two-step maneuver was successfully performed in the operating room with a single surgeon and the use of minimal force. While there is a paucity of data demonstrating significant differences between the use of GA or conscious sedation, studies have shown that closed reduction of ISD under GA results in satisfactory outcomes [8] , [9] , [10] . In similar cases with associated bony injuries and multiple reduction attempts, surgeons may prefer reducing complex dislocations in the operating room under GA with procedural fluoroscopy to avoid further injury to ensure a safe and timely reduction.…”
Section: Discussionmentioning
confidence: 99%